Etiological role and molecular-genetic features of Streptococcus pneumoniae in children's infectious diseases - I. N. Protasova; G. P. Martynova; N. A. Ilyenkova; I. A. Kutischeva; S. V. Domracheva; O. P. Ovchinnikova; E. S. Sokolovskaya (LLC "Diagnostics and Vaccines", 2020)
Objective: To study the etiological role, serotype distribution and prevalent Streptococcus pneumoniae genotypes (sequence types) in 459 children hospitalized with acute purulent otitis media, acute tonsillitis, community-acquired pneumonia, and purulent bacterial meningitis. Pneumococcal cultures isolated from patients were tested for sensitivity to antimicrobials, and presence of resistance genes.Materials and Methods: The cultural and molecular methods (PCR, sequencing) were used. Statistical analysis was carried out using Microsoft Excel 2007 and Statistica 6.0. Results: S. pneumoniae was detected in 16,8%. The prevalent serotypes were 19F (39.7%) and 19A (13.2%) - representatives of multidrug-resistant clonal com-plex 320. Isolates of serogroup 6 (6AB, 8.82%) belonged to clonal complex 315, and characterized by resistance to macrolides, clindamycin and tetracycline.From 70.6% to 88.2% of S. pneumoniae serotypes isolated from patients corresponded to «vaccine»-types.